Factors Associated With Induction of Labor Among Primiparous Women Delivering at Term in the LTM III Study [30K]. (May 2017) - Patel, Divya; Davidson, Christina; Salahuddin, Meliha; Lakey, David
Abstract : INTRODUCTION: Induction of labor (IOL) is an increasingly common obstetrical procedure in the U.S., yet characteristics associated with IOL among primiparous women delivering at term are not well understood. METHODS: Data from the Listening to Mothers III study, a survey of women ages 18-45 who delivered singleton babies in U.S. hospitals in 2011-12, were utilized. Weighted logistic regression models examined predictors of IOL among 924 primiparous women with term deliveries. Associations of maternal characteristics with delivery route (cesarean and vaginal delivery) were examined among primiparous women induced at term. RESULTS: 423 (45.8%) primiparous women who delivered at term underwent IOL; subjective/non-medical reasons were reported by 53% of induced women. Women who were married (OR=1.8), felt pressure from a provider for IOL (OR=3.5), and whose provider was concerned about size of the baby (OR=1.9) were significantly more likely to undergo IOL. Nearly 30% of primiparous women who underwent IOL at term had cesarean delivery. Among induced women, those who were overweight/obese (OR=4.9), felt pressure from a provider for cesarean delivery (OR=9.0), believed that childbirth should only be interfered with if medically necessary (OR=2.2), and whose provider suspected the baby might be getting large near end of pregnancy (OR=2.9) were significantly more likely to have cesarean delivery. CONCLUSION: In this study, nearly half of primiparous women with term deliveries underwent IOL, with a sizeable proportion reporting subjective or non-medical reasons for induction. A better understanding of characteristics associated with IOL at term may help reduce unnecessary intrapartum interventions and, ultimately, primary cesarean delivery.